Severe hemolytic and emphysematous liver abscess in patient with sepsis due to Edwardsiella tarda - Ton, Sy Q; Nguyen, Hai Q; Vu, Minh K (The Journal of Infection in Developing Countries, 2026)
Introduction: Edwardsiella tarda is a Gram-negative facultative anaerobe commonly isolated from fish and reptiles. This bacterium infrequently causes disease in humans, but the mortality rate is very high when associated with sepsis. Case presentation: This case report describes an 80-year-old female patient with Edwardsiella tarda infection who rapidly deteriorated, ultimately succumbing to infection within 9 hours after presenting to the emergency department. This patient was diagnosed with sepsis, hemolytic, emphysematous liver abscess. Conclusions: This report underscores the potential fatality and rapid progression of Edwardsiella tarda infection, highlighting the importance of early recognition and intervention.